Determinan Kualitas Informasi Pelaporan Keuangan Di Kota Langsa - Lolita Putri Susanti Siregar; Nasrul Kahfi Lubis; Agustina Nurul Fajriah (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
This research aims to assess how internal control, information technology, and staff competence influence the quality of financial reporting in Kota Langsa. The research methodology employed is quantitative, utilizing primary data. All Local Government Units (OPD) in Kota Langsa, totaling 33, were taken as the sample, with three respondents from each OPD, resulting in a total of 99 respondents. The sample selection was done through purposive sampling.Data were collected through questionnaire distribution and the use of measurement tools such as validity and reliability tests. Data analysis employed multiple linear regression analysis, with hypothesis testing using t-tests and F-tests. The regression analysis results indicated that internal control has a significant positive influence on the quality of financial information in the reports. Conversely, information technology does not have a significant impact, while staff competence also has a significant positive effect.In summary, this research demonstrates that internal control and staff competence play vital roles in enhancing the quality of financial reporting in Kota Langsa, whereas information technology does not have a significant impact